Diversity and population connectivity of members of the family Eunicidae inhabiting deep-water corals in the North Atlantic - Carlota Gracia-Sancha; Nicolai Roterman; Michelle L. Taylor; Kerry L. Howell; Alex D. Rogers; Sofía Ruiz-Cano; Sergi Taboada (Molecular Phylogenetics and Evolution, 2026)

Refugia, but Not for Everyone: Genetic Structure Differentiates Shallow and Mesophotic Populations of the Brooder Sponge Ircinia variabilis - Tom Morav; Micha Ilan; Liron Goren; Tal Idan; Sigal Shefer; Yaron Tikochinski; Julio A. Díaz; Giorgos Chatzigeorgiou; Carlota Gracia‐Sancha; Ana Riesgo; Sergi Taboada (Molecular Ecology, 2026)
Understanding how gene‐flow and selection interact across environmental gradients is essential for assessing population resilience and evaluating the deep‐refugia potential of mesophotic habitats under rapid climate change. In the context of depth, genetic connectivity patterns have been documented for broadcast‐spawning species, but that of brooding marine invertebrates remains largely unexplored, leaving the role of mesophotic habitats as potential refugia uncertain. Here, we investigated the genetic structure of the brooder sponge Ircinia variabilis across shallow and mesophotic habitats in the Eastern Mediterranean and across shallow sites spanning multiple Mediterranean basins (i.e., Mallorca, Ionian‐Sea and Israel). By quantifying depth and distance‐related connectivity, and assessing the relative roles of neutral processes and temperature‐driven selection, we evaluated the genetic connectivity of I. variabilis and the potential of mesophotic habitats to function as refugia. Using ddRADseq, we obtained 957 SNPs, to characterize gene‐flow patterns, genetic structure, and environmental influences on differentiation. Ircinia variabilis exhibited pronounced vertical and geographic genetic structure, consistent with limited larval dispersal. Notably, Ionian‐Sea populations were genetically closer to Mallorca than to the geographically closer Israeli populations, suggesting influence of oceanographic barriers. Analyses of selection‐associated loci indicate that environmental variability contributes to population divergence, supporting local adaptation. Along the Israeli coast, pronounced differentiation between shallow and mesophotic populations highlights depth as a key axis of evolutionary divergence. Limited vertical connectivity challenges a central assumption of the deep refugia hypothesis, suggesting mesophotic populations may not sustain shallow populations under climate change.

Genomic Connectivity and Adaptation Signals of the Freshwater Sponge Ephydatia muelleri Across Its Distribution - Laura de la Cruz‐Castillejo; Robert Cassidy; Konstantina Mitsi; Carles Galià‐Camps; Ana Benítez‐López; Carlota Gracia‐Sancha; Jose Lorente‐Sorolla; Almudena Álvarez‐Fernández; Rocío Mozo; Stephen Kolomyjec; Scott Nichols; Renata Manconi; et al. (Journal of Biogeography, 2026)
Aim Genetic connectivity and local adaptation were examined across the distribution of the freshwater sponge Ephydatia muelleri . Because it occupies an exceptional breadth of freshwater environments across a broad geographic range, this species offers key insights into biogeographic processes shaping genetic structure and adaptation in inland waters. Location Freshwater habitats across North America, Europe and Asia. Taxon Freshwater sponges (Porifera, order Spongillida). Methods A total of 106 individuals were sampled from 11 localities across three continents. Double‐digest RADseq was used to generate genome‐wide SNP data, resulting in 3114 putatively neutral SNPs for analyses of population structure and connectivity and 115 candidate SNPs potentially under selection for assessing signatures of local adaptation to environmental variables such as light and temperature. Results Neutral loci revealed low connectivity and strong genetic differentiation among regions, with two major genetic clusters corresponding to North America and Eurasia. Loci under selection indicated polygenic adaptation to environmental gradients of light and temperature and evidence of selection on gene regulatory processes. Patterns of genetic structure are consistent with the monopolisation hypothesis, suggesting that historical processes, particularly range shifts and barriers associated with the Last Glacial Maximum, have had a stronger influence on current genetic structure than ongoing gene flow. Main Conclusions Ephydatia muelleri populations show limited dispersal and strong historical imprints on genetic structure but also exhibit adaptive responses to local environmental variation. These findings highlight how monopolisation and historical climatic events shape freshwater invertebrate biogeography. Our study provides new insights into dispersal pathways, genetic plasticity and the resilience of freshwater sponges, with implications for the conservation of freshwater ecosystems.

No Mate, No Problem: Molecular Mechanisms Involved in Parthenogenesis in the Cosmopolitan Earthworm Aporrectodea trapezoides (Annelida, Clitellata) - Irene de Sosa; Marta Turon; Sergi Taboada; José Lorente‐Sorolla; Rosa Fernández; Natasha Tilikj; Alberto Piris; Marta Novo; Patricia Álvarez Campos; Ana Riesgo (Molecular Ecology, 2025)
Approximately, 40% of earthworm species can reproduce by parthenogenesis. This is the case for the cosmopolitan species, Aporrectodea trapezoides , although sexual forms have been described sporadically. We analyse the genotypes and microbiomes of 30 individuals from four localities where both forms appear in order to understand the evolutionary mechanisms related to parthenogenesis. In all sites, heterozygosity values were approximately 30% higher in parthenogenetic individuals. However, we detected a stronger genomic structuring due to reproduction than to the geographical setting only in the Algerian population, underpinned by 195 loci that were related to gametogenesis, symbiont‐like processes, and nitrate reduction. Similarly, statistical differences in the abundance of ZOTUs were only found between the Algerian sexual and parthenogenetic earthworms, with 754 ZOTUs that included the genus Romboutsia , which is involved in the production of nitric oxide, which enhances sperm motility. In summary, significant genomic and microbiome differences were found only between sexual and parthenogenetic lineages in a single locality. We hypothesise that obligate parthenogenesis evolved early, leaving traces at the genomic and microbiome levels in the Algerian parthenogens that were the earliest splitting lineage. Such obligate parthenogenesis was lost secondarily and individuals in the Iberian sites were facultative parthenogens, with the potential to copulate and therefore erase the genomic and microbial traces of obligate parthenogenesis. Our results indicate a hybrid origin of parthenogenesis in A. trapezoides and shed light on the complex interplay between genomic, microbiome, and reproductive mechanisms in A. trapezoides .

Marked Variability in Distance‐Decay Patterns Suggests Contrasting Dispersal Ability in Abyssal Taxa - Erik Simon‐Lledó; Andrés Baselga; Carola Gómez‐Rodríguez; Anna Metaxas; Diva J. Amon; Guadalupe Bribiesca‐Contreras; Jennifer M. Durden; Bethany Fleming; Alejandra Mejía‐Saenz; Sergi Taboada; Loïc Van Audenhaege; Daniel O. B. Jones (Global Ecology and Biogeography, 2025)
Aim We assess the role of spatial distance and depth difference in shaping beta diversity patterns across abyssal seascape regions. We measured the decrease of faunistic similarity across the northeast Pacific seafloor, to test whether species turnover rates differ between deep and shallow‐abyssal biogeographical provinces and whether these patterns vary across functionally or taxonomically different biotic groups. Location Abyssal NE Pacific Ocean. Time Period Present. Major Taxa Studied Benthic Invertebrates (13 Phyla). Methods We examined the relationship between compositional similarity (𝛽 sim ) and spatial distance, distance‐decay, in benthic megafauna communities (animals > 10 mm) based on seabed imagery data (> 36,000 specimens in 402 species) collected across 28 abyssal seascape locations spanning a total of 4000 km. By comparing the statistical parameters (intercept and slope) of decay curves, we investigated whether distance‐decay patterns differ (i) between communities above and below the carbonate compensation depth (~4400 m at N Pacific), (ii) among taxa with contrasting life‐habits and (ii) across dominant phyla. Results We found steeper species turnover rates in communities below 4400 m and variations in distance‐decay patterns across biotic groups. Turnover was higher for taxa facultatively growing on hard‐substratum patches (polymetallic nodules) than for sediment‐dwelling or swimming organisms. Cnidaria and Porifera, respectively, depicted the most and least evident spatial decays in community similarity. Main Conclusions We demonstrate the utility of combining seabed imaging with distance‐decay modelling to capture macroecological patterns in poorly explored deep‐sea ecosystems. Our results suggest that chemical boundaries associated with depth are a very relevant niche‐sorting mechanism driving large‐scale beta‐diversity patterns and an association between species life‐habits and dispersal limitation in abyssal seabed communities. These findings have important implications for biodiversity conservation plans in the deep ocean, amid the need to protect vast abyssal seascape ecosystems from globally rising human threats.

Long distance dispersal and oceanographic fronts shape the connectivity of the keystone sponge Phakellia ventilabrum in the deep northeast Atlantic - Sergi Taboada; Connie Whiting; Shuangqiang Wang; Pilar Ríos; Andrew J. Davies; Furu Mienis; Ellen Kenchington; Paco Cárdenas; Alex Cranston; Vasiliki Koutsouveli; Javier Cristobo; Hans Tore Rapp; et al. (Frontiers in Marine Science, 2023)
Little is known about dispersal in deep-sea ecosystems, especially for sponges, which are abundant ecosystem engineers. Understanding patterns of gene flow in deep-sea sponges is essential, especially in areas where rising pressure from anthropogenic activities makes difficult to combine management and conservation. Here, we combined population genomics and oceanographic modelling to understand how Northeast Atlantic populations (Cantabrian Sea to Norway) of the deep-sea sponge Phakellia ventilabrum are connected. The analysis comprised ddRADseq derived SNP datasets of 166 individuals collected from 57 sampling stations from 17 different areas, including two Marine Protected Areas, one Special Area of Conservation and other areas with different levels of protection. The 4,017 neutral SNPs used indicated high connectivity and panmixis amongst the majority of areas (Ireland to Norway), spanning ca. 2,500-km at depths of 99–900 m. This was likely due to the presence of strong ocean currents allowing long-distance larval transport, as supported by our migration analysis and by 3D particle tracking modelling. On the contrary, the Cantabrian Sea and Roscoff (France) samples, the southernmost areas in our study, appeared disconnected from the remaining areas, probably due to prevailing current circulation patterns and topographic features, which might be acting as barriers for gene flow. Despite this major genetic break, our results suggest that all protected areas studied are well-connected with each other. Interestingly, analysis of SNPs under selection replicated results obtained for neutral SNPs. The relatively low genetic diversity observed along the study area, though, highlights the potential fragility of this species to changing climates, which might compromise resilience to future threats.

Unveiling biogeographical patterns in the worldwide distributed Ceratitis capitata (medfly) using population genomics and microbiome composition - María Belén Arias; Katherine Hartle‐Mougiou; Sergi Taboada; Alfried P. Vogler; Ana Riesgo; Samia Elfekih (Molecular Ecology, 2022)
Invasive species are among the most important, growing threats to food security and agricultural systems. The Mediterranean medfly, Ceratitis capitata , is one of the most damaging representatives of a group of rapidly expanding species in the family Tephritidae, due to their wide host range and high invasiveness potential. Here, we used restriction site‐associated DNA sequencing (RADseq) to investigate the population genomic structure and phylogeographical history of medflies collected from six sampling sites, including Africa (South Africa), the Mediterranean (Spain, Greece), Latin America (Guatemala, Brazil) and Australia. A total of 1907 single nucleotide polymorphisms (SNPs) were used to identify two genetic clusters separating native and introduced ranges, consistent with previous findings. In the introduced range, all individuals were assigned to one genetic cluster except for those in Brazil, which showed introgression of an additional genetic cluster that also appeared in South Africa, and which could not be previously identified using microsatellite markers. Moreover, we assessed the microbial composition variations in medfly populations from selected sampling sites using amplicon sequencing of the 16S ribosomal RNA (V4 region). Microbiome composition and structure were highly similar across geographical regions and host plants, and only the Brazilian specimens showed increased diversity levels and a unique composition of its microbiome compared to other sampling sites. The unique SNP patterns and microbiome features in the Brazilian specimens could point to a direct migration route from Africa with subsequent adaptation of the microbiota to the specific conditions present in Brazil. These findings significantly improve our understanding of the evolutionary history of the global medfly invasions and their adaptation to newly colonized environments.

On the way to specificity ‐ Microbiome reflects sponge genetic cluster primarily in highly structured populations - Cristina Díez‐Vives; Sergi Taboada; Carlos Leiva; Kathrin Busch; Ute Hentschel; Ana Riesgo (Molecular Ecology, 2020)
Most animals, including sponges (Porifera), have species‐specific microbiomes. Which genetic or environmental factors play major roles structuring the microbial community at the intraspecific level in sponges is, however, largely unknown. In this study, we tested whether geographic location or genetic structure of conspecific sponges influences their microbial assembly. For that, we used three sponge species with different rates of gene flow, and collected samples along their entire distribution range (two from the Mediterranean and one from the Southern Ocean) yielding a total of 393 samples. These three sponge species have been previously analysed by microsatellites or single nucleotide polymorphisms, and here we investigate their microbiomes by amplicon sequencing of the microbial 16S rRNA gene. The sponge Petrosia ficiformis , with highly isolated populations (low gene flow), showed a stronger influence of the host genetic distance on the microbial composition than the spatial distance. Host‐specificity was therefore detected at the genotypic level, with individuals belonging to the same host genetic cluster harbouring more similar microbiomes than distant ones. On the contrary, the microbiome of Ircinia fasciculata and Dendrilla antarctica ‐ both with weak population structure (high gene flow) ‐ seemed influenced by location rather than by host genetic distance. Our results suggest that in sponge species with high population structure, the host genetic cluster influence the microbial community more than the geographic location.

Microbial insights from Antarctic and Mediterranean shallow-water bone-eating worms - Olivia H. Hewitt; Cristina Díez-Vives; Sergi Taboada (Polar Biology, 2020)
Bone-eating worms of the genus Osedax (Annelida, Siboglinidae) form unique holobionts (functional entity comprising host and associated microbiota), highly adapted to inhabit bone tissue of marine vertebrates. These gutless worms have developed nutritional symbioses housing intracellular, horizontally acquired, heterotrophic bacteria hypothesised to harness nutrients from organic compounds, sequestered within the bone. Despite previous efforts, critical mechanisms mediating activity and acquisition of diverse bacterial assemblages remain unclear. Using 16S rRNA amplicon sequencing, we performed detailed taxonomic and predicted functional analyses shedding light on the microbial communities of two shallow-water Osedax species ( Osedax deceptionensis and Osedax ‘mediterranea’) from contrasting habitats (Antarctic and Mediterranean Sea), in two tissue types (roots and palps). Comparative assessments between host species revealed distinct microbial assemblages whilst, within host species and body tissue, relative symbiont frequencies retained high variability. We reported relatively high abundances of microbes previously classified as primary endosymbionts, Ribotype 1 (order Oceanospirillales), and diverse likely secondary epibionts warranting further exploration as recurrent Osedax associates. Surprisingly, O. ‘mediterranea’ exhibited relatively low abundance of Oceanospirillales, but increased abundance of other potentially hydrocarbon degrading bacteria from the family Alteromonadaceae. We hypothesise the presence of functionally similar, non-Oceanospirillales primary endosymbionts within O. ‘mediterranea’. Functional metagenomic profiling (using 16S rRNA sequences) predicted broad metabolic capabilities, encompassing relatively large abundances of genes associated with amino acid metabolism. Comparative analyses between host body tissue communities highlighted several genes potentially providing critical functions to the Osedax host or that confer adaptations for intracellular life, housed within bone embedded host root tissues.

Phylogenetic characterization of marine microbial biofilms associated with mammal bones in temperate and polar areas - Sergi Taboada; Maria Bas; Conxita Avila; Ana Riesgo (Marine Biodiversity, 2020)

Population substructure and signals of divergent adaptive selection despite admixture in the sponge Dendrilla antarctica from shallow waters surrounding the Antarctic Peninsula - Carlos Leiva; Sergi Taboada; Nathan J. Kenny; David Combosch; Gonzalo Giribet; Thibaut Jombart; Ana Riesgo (Molecular Ecology, 2019)
Antarctic shallow‐water invertebrates are exceptional candidates to study population genetics and evolution, because of their peculiar evolutionary history and adaptation to extreme habitats that expand and retreat with the ice sheets. Among them, sponges are one of the major components, yet population connectivity of none of their many Antarctic species has been studied. To investigate gene flow, local adaptation and resilience to near‐future changes caused by global warming, we sequenced 62 individuals of the sponge Dendrilla antarctica along the Western Antarctic Peninsula (WAP) and the South Shetlands (spanning ~900 km). We obtained information from 577 double digest restriction site‐associated DNA sequencing (ddRADseq)‐derived single nucleotide polymorphism (SNP), using RADseq techniques for the first time with shallow‐water sponges. In contrast to other studies in sponges, our 389 neutral SNPs data set showed high levels of gene flow, with a subtle substructure driven by the circulation system of the studied area. However, the 140 outlier SNPs under positive selection showed signals of population differentiation, separating the central–southern WAP from the Bransfield Strait area, indicating a divergent selection process in the study area despite panmixia. Fourteen of these outliers were annotated, being mostly involved in immune and stress responses. We suggest that the main selective pressure on D. antarctica might be the difference in the planktonic communities present in the central–southern WAP compared to the Bransfield Strait area, ultimately depending on sea‐ice control of phytoplankton blooms. Our study unveils an unexpectedly long‐distance larval dispersal exceptional in Porifera, broadening the use of genome‐wide markers within nonmodel Antarctic organisms.

Implications of population connectivity studies for the design of marine protected areas in the deep sea: An example of a demosponge from the Clarion‐Clipperton Zone - Sergi Taboada; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Vasiliki Koutsouveli; Nadiezhda Santodomingo; Andrew C. Dale; Craig R. Smith; Daniel O. B. Jones; Thomas G. Dahlgren; Adrian G. Glover (Molecular Ecology, 2018)
The abyssal demosponge Plenaster craigi inhabits the Clarion‐Clipperton Zone ( CCZ ) in the northeast Pacific, a region with abundant seafloor polymetallic nodules with potential mining interest. Since P. craigi is a very abundant encrusting sponge on nodules, understanding its genetic diversity and connectivity could provide important insights into extinction risks and design of marine protected areas. Our main aim was to assess the effectiveness of the Area of Particular Environmental Interest 6 ( APEI ‐6) as a potential genetic reservoir for three adjacent mining exploration contract areas ( UK ‐1A, UK ‐1B and OMS ‐1A). As in many other sponges, COI showed extremely low variability even for samples ~900 km apart. Conversely, the 168 individuals of P. craigi, genotyped for 11 microsatellite markers, provided strong genetic structure at large geographical scales not explained by isolation by distance (IBD). Interestingly, we detected molecular affinities between samples from APEI ‐6 and UK ‐1A, despite being separated ~800 km. Although our migration analysis inferred very little progeny dispersal of individuals between areas, the major differentiation of OMS ‐1A from the other areas might be explained by the occurrence of predominantly northeasterly transport predicted by the HYCOM hydrodynamic model. Our study suggests that although APEI ‐6 does serve a conservation role, with species connectivity to the exploration areas, it is on its own inadequate as a propagule source for P. craigi for the entire eastern portion of the CCZ . Our new data suggest that an APEI located to the east and/or the south of the UK ‐1, OMS ‐1, BGR , TOML and NORI areas would be highly valuable.

Population structure and phylogenetic relationships of a new shallow‐water Antarctic phyllodocid annelid - Carlos Leiva; Ana Riesgo; Conxita Avila; Greg W. Rouse; Sergi Taboada (Zoologica Scripta, 2018)
Shallow‐water polychaetes are abundant and diverse components of the Southern Ocean benthic communities, and although they have been widely studied, new species that are relatively common are still discovered. Here, we report the discovery of Pterocirrus giribeti sp. n., a new and abundant intertidal and upper‐subtidal Antarctic phyllodocid. To establish the phylogenetic relationships of the new species, we sequenced two nuclear ( 18S and 28S ) and two mitochondrial ( COI and 16S ) markers. Although the phylogenetic relationships obtained for the family Phyllodocidae were not fully resolved, we assigned our new phyllodocid to the genus Pterocirrus based on both its phylogenetic position and its morphological characters. Using COI and 16S sequences of 126 and 118 individuals, respectively, from eight populations across the South Shetland Islands and the Antarctic Peninsula, we also investigated the genetic diversity and gene flow patterns of this new species. Our results suggested that all populations were panmictic, likely due to the presence of planktotrophic larvae allowing long‐distance dispersal. Interestingly, some genetic substructure was detected despite panmixis, and we identified a semipermeable barrier coinciding with an oceanic front produced by the intrusion into the Bransfield Strait of a tongue of water from the Weddell Sea. This front produced signatures of differentiation on populations at the tip of the West Antarctic Peninsula. Moreover, our results indicated a recent demographic expansion throughout the sampled area, in agreement with the “glacial refugium” hypothesis stated for other Antarctic shallow‐water invertebrates.

A new member of the genus Antarctonemertes (Hoplonemertea, Nemertea) from Antarctic waters - Sergi Taboada; Carlos Leiva; Juan Junoy; Frances Alexander; Ana Riesgo (Polar Biology, 2018)

Mitochondrial genome and polymorphic microsatellite markers from the abyssal sponge Plenaster craigi Lim & Wiklund, 2017: tools for understanding the impact of deep-sea mining - Sergi Taboada; Nathan J. Kenny; Ana Riesgo; Helena Wiklund; Gordon L. J. Paterson; Thomas G. Dahlgren; Adrian G. Glover (Marine Biodiversity, 2018)

Cryptic species and colonization processes in Ophryotrocha (Annelida, Dorvilleidae) inhabiting vertebrate remains in the shallow‐water Mediterranean - Sergi Taboada; Carlos Leiva; Maria Bas; Nancy Schult; Damhnait McHugh (Zoologica Scripta, 2017)
Over the past several years, there has been growing interest in how bones of decaying mammals are colonized in the marine seabed. One of the most common opportunistic taxa occurring worldwide on bones is dorvilleid polychaetes of the genus Ophryotrocha . In a recent study in the Mediterranean, Ophryotrocha puerilis and Ophryotrocha alborana were two of the most abundant species occurring in experimentally deployed bones. These species have direct development and this makes them a suitable model to study the mechanisms and processes allowing organisms lacking a dispersive larval phase to colonize new substrates. Here, we address the colonization processes at the molecular level for populations of O. puerilis and O. alborana on experimentally deployed mammal bones in the shallow‐water Mediterranean collected over a year at 3‐month intervals. High genetic distances between some of the O. puerilis organisms collected indicated the occurrence of at least two cryptic sibling species ( O. puerilis ‘Shallow’ and O. puerilis ‘Deep’) apart from O. puerilis sensu stricto . This was corroborated with phylogenetic analyses using an alignment of three concatenated genes ( COI , 16S , H3 ) and with species delimitation analyses using COI . The haplotype network inferred from COI sequences for O. puerilis ‘Shallow’ showed a few common haplotypes shared between the two trimesters analysed and several other less represented haplotypes only present in one trimester. Thus, colonization of these experimental bones may have been achieved by a few organisms that arrived to the bones and were able to reseed, and by several individuals arriving to the experimental bones and not persisting across time. In contrast, the haplotype network for O. alborana revealed that none of the haplotypes present in three different trimesters were shared, suggesting that the populations arriving at the bones during each trimester were totally replaced by new individuals during the subsequent trimesters. Our study suggests that different species of shallow‐water Ophryotrocha occurring in the Mediterranean may have different patterns of substrate colonization despite sharing similar life histories.

Is the Antarctic Ophryotrocha orensanzi (Annelida: Dorvilleidae) a circumpolar non-specialized opportunist? - Hannelore Paxton; Helena Wiklund; Frances Alexander; Sergi Taboada (Systematics and Biodiversity, 2017)

Lonely populations in the deep: genetic structure of red gorgonians at the heads of submarine canyons in the north-western Mediterranean Sea - Rocío Pérez-Portela; Elena Cerro-Gálvez; Sergi Taboada; Carlo Tidu; Carolina Campillo-Campbell; Joan Mora; Ana Riesgo (Coral Reefs, 2016)

Life after death: shallow‐water Mediterranean invertebrate communities associated with mammal bones - Sergi Taboada; Maria Bas; Carlos Leiva; Mariona Garriga; Rafael Sardá; Conxita Avila (Marine Ecology, 2016)
Invertebrate and microbial marine communities associated with mammal bones are interesting and poorly understood habitats, mainly known from studies on deep‐water whale remains. In order to characterize these communities in the shallow‐water Mediterranean, we present here the results of a pioneering experiment using mammal bones. Minke whale, pig and cow bones were experimentally deployed on three different background communities: rocky substrate, soft‐bottom and a Posidonia oceanica meadow. Bones were deployed for a year at about 20 m depth and collected every 3 months, and the invertebrate fauna colonizing the bones was identified to the lowest possible taxonomic level. As expected, mammal bones showed remarkable differences when compared with background communities. Within bones, four different clusters could be identified, primarily on the basis of the polychaete fauna, the most abundant and diverse group in the survey. Clusters A1–A3 corresponded to high to moderately altered successional stages composed by a fauna closer to that of anthropogenically enriched shallow‐water environments. These clusters were characterized by the occurrence of the opportunist polychaetes Ophryotrocha puerilis , Neanthes caudata (Cluster A1), Protodorvillea kefersteini (Cluster A2) and Ophryotrocha alborana (Cluster A3). Cluster B was characterized by the presence of the polychaete Oxydromus pallidus together with typical invertebrate background fauna, which suggests that this community, after a year of deployment, was closer to that found in natural conditions. As opposed to similar shallow‐water studies in other geographic areas, no occurrence of the polychaete Osedax (commonly known as bone‐eating worms) was reported from our experiments. Apart from the study on the invertebrate communities, insights about the population dynamics of three of the most abundant species ( O. puerilis , O. alborana , N. caudata ) are given as well as remarks on a hypothetical trophic network based on fecal pellet analysis.

First assessment of the rocky intertidal communities of Fildes Bay, King George Island (South Shetland Islands, Antarctica) - Ahmed Aghmich; Sergi Taboada; Lluis Toll; Manuel Ballesteros (Polar Biology, 2016)

Development of 10 microsatellite markers for the Atlanto-Mediterranean sponge Petrosia ficiformis - Sergi Taboada; Ana Riesgo; Gema Blasco; Joan Solà; Joana R. Xavier; Susanna López-Legentil (Conservation Genetics Resources, 2015)

Anti-predatory chemical defences in Antarctic benthic fauna - Juan Moles; Laura Núñez-Pons; Sergi Taboada; Blanca Figuerola; Javier Cristobo; Conxita Avila (Marine Biology, 2015)

Distribution patterns in Antarctic and Subantarctic echinoderms - Juan Moles; Blanca Figuerola; Neus Campanyà-Llovet; Toni Monleón-Getino; Sergi Taboada; Conxita Avila (Polar Biology, 2015)

A new Parougia species (Annelida, Dorvilleidae) associated with eutrophic marine habitats in Antarctica - Sergi Taboada; Maria Bas; Conxita Avila (Polar Biology, 2015)

On the identity of two Antarctic brooding nemerteans: redescription of Antarctonemertes valida (Bürger, 1893) and description of a new species in the genus Antarctonemertes Friedrich, 1955 (Nemertea, Hoplonemertea) - Sergi Taboada; Juan Junoy; Sónia C. S. Andrade; Gonzalo Giribet; Javier Cristobo; Conxita Avila (Polar Biology, 2013)

Two new Antarctic Ophryotrocha (Annelida: Dorvilleidae) described from shallow-water whale bones - Sergi Taboada; Helena Wiklund; Adrian G. Glover; Thomas G. Dahlgren; Javier Cristobo; Conxita Avila (Polar Biology, 2013)

Feeding repellence of Antarctic and sub-Antarctic benthic invertebrates against the omnivorous sea star Odontaster validus - Sergi Taboada; Laura Núñez-Pons; Conxita Avila (Polar Biology, 2013)

Triterpene glycosides from Antarctic sea cucumbers III. Structures of liouvillosides A 4 and A 5 , two minor disulphated tetraosides containing 3- O -methylquinovose as terminal monosaccharide units from the sea cucumber Staurocucumis liouvillei (Vaney) - Alexandr S. Antonov; Sergey A. Avilov; Anatoly I. Kalinovsky; Pavel S. Dmitrenok; Vladimir I. Kalinin; Sergi Taboada; Manuel Ballesteros; Conxita Avila (Natural Product Research, 2011)

Antarctic marine chemical ecology: what is next? - Conxita Avila; Sergi Taboada; Laura Núñez‐Pons (Marine Ecology, 2008)
Antarctic ecosystems are exposed to unique environmental characteristics resulting in communities structured both by biotic interactions such as predation and competition, as well as abiotic factors such as seasonality and ice‐scouring. It is important to understand how ecological factors may trigger chemical mechanisms in marine Antarctic organisms as a response for survival. However, very little is known yet about the evolution of chemical compounds in Antarctic organisms. Investigations in chemical ecology have demonstrated over the last several years that defensive metabolites have evolved in numerous representative Antarctic species. This contradicts earlier theories concerning biogeographic variation in predation and chemical defenses. As reviewed here, a number of interesting natural products have been isolated from Antarctic organisms. However, we believe many more are still to be discovered. Currently, many groups such as microorganisms, planktonic organisms and deep‐sea fauna remain almost totally unknown regarding their natural products. Furthermore, for many described compounds, ecological roles have yet to be evaluated. In fact, much of the research carried out to date has been conducted in the laboratory, and only in a few cases in an ecologically relevant context. Therefore, there is a need to extend the experiments to the field, as done in tropical and temperate marine ecosystems, or at least, to test the activity of the chemicals in natural conditions and ecologically meaningful interactions. Defense against predators is always one of the main topics when talking about the roles of natural products in species interactions, but many other interesting aspects, such as competition, chemoattraction, fouling avoidance and ultraviolet (UV) protection, also deserve further attention. In our opinion, challenging future developments are to be expected for Antarctic marine chemical ecology in the years to come.

Simultaneous genotyping of CYP2C9*2, *3, and 5′ flanking region (C-1189T) polymorphisms in a Spanish population through a new minisequencing multiplex single-base extension analysis - Sergi Mas; Anna Crescenti; Jose M. Vidal-Taboada; Salvador Bergoñon; Fernando Cuevillas; Nuria Laso; Rafael Molina; Antonio Ballesta; Amalia Lafuente (European Journal of Clinical Pharmacology, 2005)